Analisis Sistem Monitoring dan Perancangan Alat Pendeteksi Kemiringan Tiang Listrik Dan Kerusakan Lampu Penerangan Jalan Umum (LPJU) Berbasis Internet of Things (IoT) - Resky, Andi Muhammad; Wardi, Wardi; Arda, Abdul Latief (Fakultas Teknik Universitas Muhammadiyah Parepare (FT-UMPAR), 2025)
This study aims to design and implement an Internet of Things (IoT)-based monitoring system for detecting electric pole tilt and Public Street Lighting (LPJU) failures. Stable pole structures and optimal street lighting are critical to ensure public safety and comfort, especially at night. However, manual inspections are inefficient and often fail to provide early detection of infrastructure damage. The system was developed using NodeMCU ESP8266 integrated with a potentiometer-based tilt sensor and a voltage sensor. The sensors acquire data on pole tilt and LPJU status, which are transmitted via Wi-Fi to a web-based monitoring application. Experimental procedures were carried out through laboratory testing and limited field simulations to evaluate both hardware and software performance. The test results show that the tilt sensor provides a linear response between the tilt angle and the output voltage, allowing accurate detection of pole inclination. In addition, the system successfully identified LPJU conditions (on/off) and displayed them in real-time on the monitoring dashboard. In conclusion, the proposed IoT-based monitoring system has proven reliable in detecting pole tilt and LPJU failures. This approach not only improves the efficiency of infrastructure maintenance but also contributes to the development of smart city solutions through more advanced and real-time monitoring technologies